Effects of oral cysteine leukotriene receptor antagonist-montelukast on adenoid lymphoid tissue: a histopathological study under light microscope - Wang, Zhengying; Wu, Xiuling; Liu, Jinghong; Wang, Yu; Zhang, Yue; Wu, Yan; Kang, Yingxue; Zhang, Ronghai; Li, Jin; Liu, Delong (Frontiers in Pharmacology, 2023)
Background: Adenoidal hypertrophy (AH) is one of the most common causes of upper airway obstruction in children. Drug and surgical treatment are the typical treatment of AH. The study on the inflammatory mechanism of AH in children provides a new idea for preoperative intervention and non-surgical treatment with anti-inflammatory drugs such as montelukast sodium (a cysteine leukotriene receptor antagonist). The aim of this study is to evaluate the effect of montelukast sodium on adenoidal lymphoid tissue pathology in children with AH under light microscope. Objective: To study whether there is any change in pathology of the adenoidal lymphoid tissue under the light microscope compared with the control group in children with moderate to severe simple AH treated with montelukast sodium for 1 month before operation. Materials and methods: Twenty patients (8 males, 12 females, 3–8 years old) with moderate to severe AH who were prepared for surgical treatment were selected. All the patients were examined by Nasopharyngeal CT and hemocyte analysis before operation. 20 subjects were randomly divided into two groups: One group was given montelukast chewable tablets 5 mg/d, qn, for 4 weeks; The control group was given placebo 5 mg/d, qn, for 4 weeks. After 4 weeks, the adenoids were removed and examined histopathology. Results: Compared with the control group, the number of lymphocytes in the blood cell analysis of the study group was significantly reduced, with a statistically significant difference (p < 0.05). And the number of germinal centers in adenoid tissue of the study group was relatively reduced, no small cyst was found in the epithelium, and the degree of inflammatory cell infiltration was reduced, with a statistically significant difference (p < 0.05). Conclusion: Montelukast can reduce the number of reactive cells, the number of lymphocytes in blood cells and blood vessels in adenoid lymphoid tissue, which can provide a new idea for preoperative intervention and non-surgical treatment of adenoid hypertrophy in children. However, this is only a pilot study and a longer treatment period is needed to assess the long-term effects of montelukast sodium on adenoid lymphoid tissue. Clinical Trial Registration: www.Chictr.org.cn, identifier ChiCTR2300075040.